Proactive management of amphibians: Challenges and opportunities. (August 2019) - Sterrett, Sean C.; Katz, Rachel A.; Brand, Adrianne B.; Fields, William R.; Dietrich, Andrew E.; Hocking, Daniel J.; Foreman, Tasha M.; Wiewel, Amber N.M.; Campbell Grant, Evan H.
Abstract: Delaying species management reduces the chance of successful recovery, increases the risk of extinction, and can be expensive. Acting before major declines are realized affords access to a greater suite of cost-effective management actions to sustain populations, reducing the likelihood of declines warranting protected status. It is clear that reactive management approaches are not sufficient for amphibian conservation and a successful path forward will require proactive approaches. We describe how conservation timelines and structured decision making can help evaluate management options available to species given current, and often limited, knowledge about populations or distributions. We illustrate this framework by highlighting science and management of common and widespread amphibians, as many species are in decline, including those found in protected conservation areas. Formal decision-making processes require the development of explicit management objectives, management triggers, and evaluation of the cost-effectiveness of actions before species' declines are observed. These steps guide the science needed to inform decisions. Highlights: Reactive conservation is inefficient, risky and potentially ineffective A lack of data for amphibians creates a challenge for proactive conservation decision making We describe how a conservation timeline can be used to evaluate proactive management strategies Conservation science requires management objectives, triggers, and improved predictions of long-term cost-effectiveness